Milton Santos' perspective and critical analysis of corporate planning of the territory (PerCursos, 2022)
This paper seeks to analyze the contribution of the geographer Milton Santos to the field of territorial planning. Therefore, an assessment is drawn concerning the main theoretical and methodological contributions that have been developed and disclosed into research agendas, taking approaches and categories based on Milton’s work as reference. Thus, it is observed that the perspective of planning as a technical matter, under the premises of neutrality, has been used to subject the developing (or peripherical) countries to the dictates of a globalization that increasingly exploits natural resources and the population’s social conditions. From this point of view, it is considered that the territorial planning has been used as a common thread of the global capitalist doctrine, in a verticalized and, imported process, in the Brazilian socio-spatial constitution, conducted by corporate agents. Through the analyses and the categories suggested by Milton, this work  addresses the main causes and consequences of the aforementioned process. Suggesting a close look at the concept of territory, taking into consideration the scale of the socio-spatial constitution, this paper also highlights the reasons that have led to the increasingly corporate use of the territory.
Keywords: Milton Santos; territorial planning; corporate use